Analysis of the Use of Project-Based Learning Model in Enhancing the Activeness of Grade IX Students at MTs 01 Darussalam Kepahiang - Inten Emilya; Nurlaili Nurlaili (JURNAL PENDIDIKAN IPS, 2025)
Islamic Religious Education (PAI) in Islamic boarding schools is often delivered conventionally and tends to limit student engagement. This study aims to analyze the implementation of the Project-Based Learning (PjBL) model in enhancing the activeness of ninth-grade students at MTs 01 Darussalam Kepahiang. This research employed a descriptive qualitative approach with data collected through observation, interviews, and documentation over a two-week period. The results indicate that the PjBL model had a positive impact on students’ activeness across cognitive, affective, and psychomotor domains. Students became more engaged in discussions, confident in expressing ideas, and creative in completing projects such as creating digital da’wah media and simulating worship practices. Teachers acted as facilitators who guided students throughout the learning process. The model fostered a more interactive and contextual learning environment. It is recommended that teachers receive training on PjBL, learning projects be made more varied, and supporting facilities be improved to enhance more effective and meaningful learning.